A multicentre prospective study of post‐traumatic endophthalmitis. (7th February 2012) - Cornut, Pierre‐Loïc; Youssef, El Bichara; Bron, Alain; Thuret, Gilles; Gain, Philippe; Burillon, Carole; Romanet, Jean‐Paul; Vandenesch, François; Maurin, Max; Creuzot‐Garcher, Catherine; Chiquet, Christophe; ,
Abstract: Purpose: Study the clinical and microbiological characteristics and the prognostic factors of post‐traumatic endophthalmitis. Methods: Seventeen eyes were included between 2004 and 2010, with clinical and microbiological data collected prospectively. Conventional cultures and panbacterial PCR were performed on aqueous and vitreous samples. Results: Clinical signs of endophthalmitis were observed soon after trauma (1.5 ± 2.5 days). Laceration with an intraocular foreign body (IOFB) was noted in 53% of the patients. At admission, all patients had aqueous humour (71%) and/or vitreous (53%) samples. Fifteen patients (88%) underwent a pars plana vitrectomy. Bacteria were identified in 77% of the cases: Staphylococcus epidermidis ( n = 5), Streptococcus ( n = 4), Bacillus ( n = 2), Pseudomonas stuzeri ( n = 1), and Streptococcus salivarius and Gemella haemolysans (multibacterial infection, n = 1). Progression toward phthisis was observed in 35% of the cases; 41% of the patients recuperated visual acuity (VA) ≥20/40. A good final visual prognosis (≥20/40) was significantly associated with initial VA better than light perception (0% versus 70%, p = 0.01) and absence of pupillary fibrin membrane (80% versus 20%, p = 0.05). There was no correlation between visual prognosis and age, the type of laceration (corneal or scleral) or presence of an IOFB. We found a statistical trend toward an association between bacterial virulence and poor final VA. Conclusion: This series showed that better final VA outcomes were associated with initial VA better than light perception, S. epidermidis or culture‐negative cases and absence of retinal detachment during the clinical course.